Application exercise depending on the performance index of neuro-spinal and spinal function of degree of compression of the vertebrae in patients with osteoporosis - Ignatiev, A. M.; Ermolenko, T. A.; Turchin, N. I.; Prutiyan, T. L.; Shanygin, A. V. (Journal of Education, Health and Sport, 2015)
Ignatyev A. M., Ermolenko T. A., Turchin N. I., Prutiyan T. L., Shanygin A. V. Подбор комплекса упражнений в зависимости от показателей индекса нейро-спинальной функции позвоночника и степени компрессии позвонков = Application exercise depending on the performance index of neuro-spinal and spinal function of degree of compression of the vertebrae in patients with osteoporosis. Journal of Education, Health and Sport. 2015;5(10):234-243. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32806 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A234-243 https://pbn.nauka.gov.pl/works/663113 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015. ПОДБОР КОМПЛЕКСА УПРАЖНЕНИЙ В ЗАВИСИМОСТИ ОТ ПОКАЗАТЕЛЕЙ ИНДЕКСА НЕЙРО-СПИНАЛЬНОЙ ФУНКЦИИ ПОЗВОНОЧНИКА И СТЕПЕНИ КОМПРЕССИИ ПОЗВОНКОВ Application exercise depending on the performance index of neuro-spinal and spinal function of degree of compression of the vertebrae in patients with osteoporosis А. М. Игнатьев, Т. А. Ермоленко, Н. И. Турчин, Т. Л. Прутиян, А. В. Шаныгин A. M. Ignatyev, T. A. Ermolenko, N. I. Turchin, T. L. Prutiyan, A. V. Shanygin Одесский национальный медицинский университет Odessa National Medical University Summary The study involved 250 patients with varying degrees of severity OP and Op, aged 19 to 89 years (49 men and 201 women). The selection criteria for the study was the presence of a verified diagnosis of OP and Op. As treatments the patients were divided into three groups: general clinical group A (n = 81) - involved the use of physiotherapy combined with standard drug therapy scheme; main clinical group B (n = 109) - for the treatment and physiokinesis DENS- used in conjunction with a standard regimen of drug treatment; the control group (n = 60) - used standard medical therapy. It was found that the combined application DENS- and physiotherapy combined with bone-seeking agents improves BMD, reduces pain, improves the "quality" of bone tissue. A set of exercises for the treatment of persons with reduced BMD varying degrees of severity. Key words: osteoporosis, osteopenia, kinesiotherapy, neuro-spinal Index. Реферат Обследовано 250 пациентов с различной степенью выраженности ОП и Оп, в возрасте от 19 до 89 лет (49 мужчин и 201 женщина). Критерием отбора для исследуемых было наличие верифицированного диагноза ОП и Оп. По методам лечения пациенты были разделены на три группы: основная клиническая группа А (n = 81) - включала использование кинезиотерапии в сочетании со стандартной схеме медикаментозной терапии; основная клиническая группа Б (n = 109) - для лечения применялась ДЕНС- и кинезиотерапия в комплексе со стандартной схемой медикаментозного лечения; контрольная группа (n = 60) - применялась стандартная медикаментозная терапия. Установлено, что комплексное применение ДЕНС- и кинезиотерапии в сочетании с остеотропными препаратами способствует повышению МПКТ, снижает болевой синдром, улучшает «качество» костной ткани. Разработан комплекс лечебных упражнений для лиц с пониженной МПКТ разной степени выраженности. Ключевые слова: остеопороз, остеопения, кинезиотерапия, нейро-спинальный индекс.